The role of regional networks in regional policy: European experience and perspectives for Russia - Igor Arzhenovsky; Natalia Solodkova (European Regional Science Association (ERSA), 2003)
The processes of globalization and localization as frame conditions of regional development cause some radical changes of spatial organization of economy and regional policy. One of such alteration is a widespread horizontal method (in addition to traditional hierarchical form) of relationship between different firms, organizations and other partners through informal contacts, intensive informational flows and cooperation skills. The report concerns theoretical substantiation, essence, different types of the regional networks as a part of regional governance and also the integration perspectives of the network method in Russian regional policy. The research is made within scientific cooperation of University of Applied Sciences Cologne, Rhine-Westphalia Institute for Economic Research, Essen, Nizhny Novgorod State University of Architecture and Civil Engineering (International Institute of Economics, Law and Management) with support of Heinrich Hertz-Stiftung, Duesseldorf. This paper deals with the regional networks as a form of free-willing, equal in rights regional cooperation and simultaneously as a decentralize form of management and organization of places. We emphasize on three main types of regional networks: 1. regional networks of enterprises and organizations 2. regional networks of enterprises and organizations with participation of authorities 3. regional networks of cities and other places The great theoretical and empirical experience in creation of the networks is accumulated in countries of the European Union. And as we see this fields, the most investigated (as in practice and also in theory) part is the regional networks of enterprises and organizations and the less studied part is regional networks of cities and other places. The networks are not a well-known tool in Russian regional policy. Some authors suggest that regional networks deserve attention as an instrument for efficient opening and use of regional socio-economical potential. An introduction of the networks in Russia means clarification of the following questions: -frame conditions and potential barriers of networks creation in Russian regions; -specific character of Russian regional networks; -the meaning of the networks in regional policy on the federal and regional level; -the influence of the networks on efficiency of such regional policy fields as structural, industrial and innovation policy; -the role of the networks in regional marketing and improvement of regional investment climate. In inference of the report the conclusion draws an attention to an unquestionable availability of the network methods in solution of regional problems. The concept of regional networks can and must become one of the modern instruments of Russian regional policy that contributes to stable regional development.
Keywords: 330